Thermo-mechanical processing and testing of titanium alloys for potential dental applications - Nape, Kgetjepe Tlhologelo (University of the Witwatersrand, Johannesburg, 2022)
New titanium alloy compositions were identified for potential dental implants on the basis of having two-phase microstructures for good mechanical properties and by avoiding problematic elements to increase biocompatibility. The Thermo-Calc program with the TTTI3 (TT Ti-alloy) database was used to calculate new Ti compositions, without toxic Al and V as alloying elements. The aim was to mimic the α+β phase proportions in Ti-6Al-4V and Ti-10.1Ta-1.7Nb-1.6Zr (TTNZ) (an analogue for Ti-6Al-4V). Copper (Cu = 1, 3, 5 and 10 wt%) was varied to give the Ti2Cu phase, which gives good hardness and antibacterial properties. A cost analysis was done and the less expensive Ti-6Nb-4Zr-xCu and Ti-8Nb-4Zr-xCu (x = 0 and 5 wt%) compositions were selected for experimental work. The samples were made by arc-melting and prepared for microstructural studies to understand the influence of alloying elements, and to compare with the commercial Ti-6Al-4V and reported Ti-10.1Ta-1.7Nb-1.6Zr (TTNZ) alloys. Hot deformation of the as-received Ti-6Al-4V and TTNZ alloys was investigated, using a Gleeble 3500® Thermo-mechanical Simulation Facility, at 850°C and 950°C and strain rates of 0.1 s-1 and 10 s-1. The as-cast Ti-6Nb-4Zr-xCu and Ti-8Nb-4Zr-xCu (x = 0 and 5 wt%) alloys comprised αTi and βTi, with Ti2Cu once Cu was added, although EDX indicated some inhomogeneity. The XRD analyses identified αTi and small amounts of βTi with solid solution (shifted peaks), with some Ti2Cu. The Ti-8Nb-4Zr alloy (285 ± 7 HV) had similar hardness to Ti-6Nb-4Zr (280 ± 13 HV), and was considered the better alloy. Adding 5 wt% Cu increased the hardness due to Ti2Cu. With the Gleeble, deformation at 950°C and 10 s-1 led to a finer Ti-6Al-4V microstructure, whereas finer Ti-10.1Ta-1.7Nb-1.6Zr (TTNZ) microstructures occurred at 850°C and 10 s-1. The XRD of all deformed Ti-6Al-4V and Ti-10.1Ta-1.7Nb-1.6Zr samples indicated αTi and βTi, with shifted βTi peaks. The Ti-6Al-4V (324 ± 9 HV) deformed at 850°C and 0.1 s-1 had higher hardness than both deformed TTNZ samples. Higher flow stress were obtained at higher strain rate (10 s-1) and lower temperature (850°C). The Ti-6Al-4V alloy had higher flow stress than the TTNZ alloy. Therefore, the TTNZ alloy was considered better, due to its lower flow stress, which indicated better formability. The new alloys had similar hardnesses to Ti-6Al-4V, and were higher than for TTNZ, suggesting that they might have similar properties to Ti-6Al-4V.
Research report submitted for the award of Masters of Science to Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022.
Keywords: New titanium alloy compositions; Thermo-Calc program; TTTI3 (TT Ti-alloy) database; Thermo-mechanical Simulation Facility; TTNZ alloy; UCTD; SDG-11: Sustainable cities and communities